Dynamic knee joint valgus - the result of a specific neuromuscular pattern during sidecutting manoeuvres in young female elite athletes? - Zebis, M. K.; Bencke, J.; Petersen, M. B.; Curtis, D.; Bloch-Lauridsen, H.; Hölmich, P.; Andersen, L. L.; Myklebust, G.; Aagaard, P. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Identifying risk factors for future ACL-injury is a promising way towards effective injury prevention. Dynamic lower extremity valgus has been identified to predict ACL-injury risk in female athletes (Hewett et al., 2005). Similar, the neuromuscular activity of agonistantagonist knee joint muscles has been identified as a potential risk factor (Zebis et al., 2009). In the present study we investigated the association between knee valgus positioning and the underlying neural pre-activation pattern in medial (m. semitendinosus) vs. lateral (vastus lateralis) thigh muscles, in a movement associated with non-contact ACL-injury. The present investigation involved a population of young female elite athletes, known to be at high risk of sustaining non-contact ACL-injury (Lind et al., 2009). Methods: Forty young female elite handball and soccer players (age 15.9 ± 1.4 years) agreed, with their parent`s consent, to participate. Five repetitions of each player`s individual sidecut manoeuvre were investigated using an 8 camera Vicon 612 system and an AMTI force platform. Knee abduction (valgus) angle at initial contact (IC) was measured. Vastus lateralis (VL) and semitendinosus (ST) muscle activity (EMG) was measured in the 50 ms time interval prior to foot strike. EMG activity was normalized to peak EMG amplitude recorded during MVC, and VL minus ST preactivity was calculated. Results: The players were divided into a valgus or a varus group based on frontal plane knee joint angle at IC. Sixteen players landed in a knee valgus position (-1.7 ± 0.8°) and 24 players in a varus position (3.7 ± 2.4°) (P<0.0001). Valgus players showed larger VL minus ST EMG values compared with varus players (20 ± 18% vs. 1 ± 23%) (P=0.004). Discussion: During rapid sidecutting, substantial neural pre-activation of the medial hamstring muscle (ST) is important to medially compress the knee joint and thereby limit the risk of excessive knee valgus positioning. The present data suggest that the occurrence of knee joint valgus during sidecutting is the result of reduced pre-activity in ST accompanied by high lateral quadriceps activity in the initial landing phase, altogether resulting in a movement profile with high risk of ACL-injury